Keratin 8 and hemidesmosomes – roles in colorectal cancer growth and mechanotransduction - Minkkinen, Mira (My University, 2023)
Keratins (Ks) are intermediate filament proteins that form a part of the cytoskeleton in intestinal epithelial cells. They provide the cells mechanical resilience against stresses caused by smooth muscle movements and intraluminal contents. Keratins can be divided into two types, type I and II, which form obligatory heterodimers with each other in a cell and tissue specific manner. K8 is the only type II keratin expressed in human intestinal epithelial cells, where it pairs with type I keratins K18, K19 and K20. In addition to providing cells mechanical resilience, keratins are also part of adhesion structures called hemidesmosomes (HDs). HDs anchor the epithelial cells to the underlying basement membrane by linking the keratin networks to the extracellular laminins through a transmembrane integrin α6β4 and a linker protein called plectin. K8 and HDs have been shown to be important for maintaining intestinal epithelial integrity and protecting the colon against colitis and experimental colorectal carcinoma (CRC) in full body and intestinal specific knockout (KO) mouse models. However, there is a lack of consensus on how K8 and HDs affect colorectal tumorigenesis and CRC growth. Further, it has not been extensively studied if HDs have a role in colonic mechanotransduction, in which cells use mechanosensors to sense mechanical stimuli in their environment and respond to them with altering different signaling pathways. The objective of this thesis was to evaluate the role that K8 and HDs have on CRC growth by utilizing the chorioallantoic membrane (CAM) model and two Caco-2 colorectal adenocarcinoma cell lines deficient in K8 and plectin, respectively. The plectin KO cells were also used to study mechano-transductional properties of the cells using liquid shear stress-induced mechanical stimuli. The results of this thesis show that all the used Caco-2 cell lines form tumors in the CAM model. However, depleting K8 in these cells inhibits tumor growth, producing smaller tumors than cells with K8. On the contrary, depletion of plectin in Caco-2 cells enhances tumor growth when analyzed against their wild type counterparts. The results further suggest that the levels of p53 tumor suppressor protein, integrin β4 and E-cadherin, all of which have major roles in cancer, could explain the differences in tumor growth between the genotypes. Plectin KO cells also exhibit morphological characteristics, namely attachment difficulties, severed keratin networks and irregular shape of the nuclei. These characteristics may affect the cells’ mechanical properties since the mechanically activated Yes-associated protein (YAP) has the highest activation in plectin depleted cells under liquid shear stress. Based on the initial results in this thesis, further research is needed to study the molecular mechanisms that are responsible for the effects of K8 and plectin on CRC growth. Next step would be to identify which signaling pathways are affected and what kind of role their interactions with K8 and HDs have on tumorigenesis, invasion, and metastasis potential of CRC. Also, an intriguing topic of study would be to deeper evaluate how the cytoskeleton, mechanotransduction and CRC growth are all related to each other. Intestinal epithelial cells respond to mechanical and biochemical cues in their environment, which are known to be altered during colorectal tumorigenesis. Mechanically resilient keratin networks and mechanically sensitive HDs could have a role in CRC growth at the interface of colorectal tumorigenesis and tumor environment.
Keywords: keratin, hemidesmosome, colorectal cancer, mechanotransduction